Friends or Foes: Is Empathy Necessary for Moral Behavior?. (September 2014) - Decety, Jean; Cowell, Jason M.
In the past decade, a flurry of empirical and theoretical research on morality and empathy has taken place, and interest and usage in the media and the public arena have increased. At times, in both popular culture and academia, morality and empathy are used interchangeably, and quite often the latter is considered to play a foundational role for the former. In this article, we argue that although there is a relationship between morality and empathy, it is not as straightforward as apparent at first glance. Moreover, it is critical to distinguish among the different facets of empathy (emotional sharing, empathic concern, and perspective taking), as each uniquely influences moral cognition and predicts differential outcomes in moral behavior. Empirical evidence and theories from evolutionary biology as well as developmental, behavioral, and affective and social neuroscience are comprehensively integrated in support of this argument. The wealth of findings illustrates a complex and equivocal relationship between morality and empathy. The key to understanding such relations is to be more precise on the concepts being used and, perhaps, abandoning the muddy concept of empathy.